A Translation Study on School Signboards in Surakarta: Types, Functions, And Quality - Ardianna Nuraeni; Fenty Kusumastuti; M.R. Nababan (Humaniora, 2016)
This research aims to map out types of bilingual signboards found in Elementary and Secondary schools in Surakarta based on their functions, to assess their quality in terms of accuracy and acceptability, and to describe factors influencing the translation quality. This descriptive qualitative research used data sources in the form of documents and persons, i.e. bilingual signboards displayed on school walls and those called raters who have competencies in assessing translation quality. Content analysis, Interview, and Focus Group Discussion were applied as the methods to collect and analyze the data of bilingual signboards. As a result, there are three types of school signboard, namely signboards showing names of place, signboards showing the condition of a particular place, and those saying proverbs. Dealing with the function, signboards having informative, suggestive, restrictive and mandatory functions are identified. The majority of the data resulting accurate and less acceptable translation is found in universal signboards, while culture-bound signboards tend to be rendered less accurate and less acceptable due to some factors that can be read thoroughly in this article.